Effect of PGPR and Cow Manure on Growth and Yield of Purple Eggplant (Solanum melongena L.) - Andriana Ela Saputri; Djarwatiningsih; Guniarti (Nusantara Science and Technology Proceedings, 2021)
The less intensive cultivation of eggplant (Solanum melongena L.) and the occurrence of soil degradations are the causes of the decline in eggplant production. Therefore, more environmentally friendly effort are needed to increase eggplant production by using PGPR and cow manure. PGPR will work optimally when combined with organic materials sourced from cow manure as nutrients trident for PGPR activity. The research was conducted from April to July 2021, in Plesungan village, Kapas District, Bojonegoro Regency, Jawa Timur. The research used a split plot design (RPT) with 16 treatment combinations and 3 replications. There are 48 trial plots. The sub plot was consentration PGPR (R) with 4 levels and dose of cow manure (K) as a main plot with 4 levesl. The data were analysed using the test of Duncan Multiple Range Test (DMRT) with a level of 5%. The result showed that there was an interaction between PGPR and cow manure. Treatment combination K3R3 (15 ton/ha cow manure + 30% NPK 15-15-15 dan 30 ml/l PGPR) increased the average plant height 17 day after planting by 2,80% and K3R2 (15 ton/ha cow manure + 30% NPK 15-15-15 dan 20 ml/l PGPR) increased the average total fruit weight of plant by 1,09%. PGPR was not significantly different in most of the parameters. Meanwhile, cow manure was significantly different in most of parameters.